2021
DOI: 10.1002/jbm.a.37250
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the molecular weight of chitosan on the tissue inflammatory response

Abstract: The molecular weight of chitosan (CS) may affect its physical properties and its ability to induce an appropriate host response. The biocompatibilities of CS membranes of low (LMWCS) and high (HMWCS) molecular weight were investigated by inserting these materials into the subcutaneous tissue of rats for 1-28 days and evaluating leukocyte infiltration, granulation tissue, fibrosis, arginase-1 immunostaining, as well as nuclear factor-κB (NF-κΒ) and fibroblast growth factor (FGF)-2 expressions. Both CS membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The anti-inflammatory effect of chitosan against IBD and UC has been reported in previous studies [ 59 ] where high-molecular-weight chitosan had better therapeutic effects in UC compared with-low molecular-weight chitosan [ 60 ]. On the other hand, an increase in the molecular weight of chitosan could result in a decline in the drug release which could be due to the greater viscosity of the gel layer created around the drug particles upon contact with the dissolution medium [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The anti-inflammatory effect of chitosan against IBD and UC has been reported in previous studies [ 59 ] where high-molecular-weight chitosan had better therapeutic effects in UC compared with-low molecular-weight chitosan [ 60 ]. On the other hand, an increase in the molecular weight of chitosan could result in a decline in the drug release which could be due to the greater viscosity of the gel layer created around the drug particles upon contact with the dissolution medium [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 81%
“…Overall, results from the in vivo studies demonstrated that all prescribed formulations significantly are effective in colitis treatment. A decrease in inflammation in CN-treated rats could be related to the anti-inflammatory effects of chitosan in IBD [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…It also seems that the rather pro- or anti-inflammatory action of chitosan is highly dependent on its molecular weight, preparation method, and the previous stimuli to which the cells were exposed . When implanted in rats, chitosan membranes with a lower molecular weight showed a reduced inflammatory response compared to higher molecular weight membranes . The chitosan used in the polyelectrolyte coatings may therefore contribute, at least partially, to the elevated TNF observation.…”
Section: Resultsmentioning
confidence: 99%
“…Under in vivo , more intensive synthesis of collagen was observed on low molecular chitosan than on high molecular weight chitosan what was associated with a prior reduction of the inflammatory response and improved wound healing. 56 TIMP-1 as a collagen degradation blocking factor was the most active after 1 day on samples with lower molecular weight (PCL45). An additional activity increase was observed on samples with higher crystallinity and lower wettability (PCL45w, PCL80w).…”
Section: Discussionmentioning
confidence: 99%